Environmental assessment of maize production alternatives: Traditional, intensive and GMO-based cropping patterns - Rotolo, Gloria Claudia; Francis, C.A.; Craviotto, Roque Mario; Ulgiati, Sergio (2018)
The evolution of maize production patterns in Argentina is evaluated over the last 25 years to compare costs, benefits, environmental performance and sustainability as well as to identify the main driving sources and improvement potential. Results from Argentina cropping systems are compared to other systems worldwide in order to put the Argentina results in a broader context. The study focuses on three farming categories: (1) traditional, low-intensity systems, (2) conventional, high-intensity systems, and (3) GMO-based cropping systems. Low input intensity systems include traditional cropping patterns with seed selection by farmers and conventional hybrid seed coupled to plowing and crop-animal rotation techniques; high input intensity systems use conventional hybrid seeds and recommended chemicals, irrigation and machinery with important soil erosion consequences; and GMO-based cropping systems use herbicide resistant transgenic hybrids, pesticides, higher fertilizer rates, and no-till practices. In each of the three cases, input flows are compared to the achieved yield (in mass and income terms) to better understand relative efficiencies and options for improvement. The study of GMO systems required a preliminary investigation of GMO seed production by seed companies, where a large investment in terms of prior knowledge and high-tech laboratory research is required. The assessments used the Emergy Accounting (EMA) approach. EMA includes material, energy, labor, money, and knowledge flows into the assessment and expands its focus over larger time and spatial scales than conventional economic and cumulative energy demand methods. Emergy-based environmental indicators of grain production for high-intensity hybrid and GMO systems both show a lower performance than low-intensity, traditional patterns in terms of resource return, renewability and sustainability. The fraction of renewability in low-intensity systems is between 28% and 63%, while it is between 8% and 26% for high-intensity hybrid and GMO systems. Calculated indicators also show that GMO-based maize production patterns do not guarantee the expected improvement over conventional high-intensity cropping systems or low-intensity systems in terms of performance and sustainability. Strong reliance on nonrenewable resources and technology, as well as role of direct and indirect labor costs are important factors in determining long-term sustainability and environmental stability of maize production systems.